Management of renin-angiotensin-aldosterone system inhibitors in patients with chronic cardiovascular conditions and its association with clinical outcomes. (3rd October 2022) - Jimenez-Marrero, S; Cainzos-Achirica, M; Monterde, D; Enjuanes, C; Garay, A; Moliner, P; Alcoberro, L; Yun, S; Ras, M; Ramos, R; Calero, E; Hidalgo, E; et al.
Abstract: Background: In chronic cardiovascular diseases, the renin-angiotensin-aldosterone system inhibitors (RAASI) are one of the keystones of the medical treatment and have revealed improvements in clinical outcomes in many clinical trials. In contrast, is well defined as non-desirable effect of RAASI the development of hyperkalemia, which could force to interrupt these treatments. Hyperkalemia has been associated with worse outcomes in observational studies. Though, it is controversial if those negative outcomes in hyperkalemic patients could be because the potassium derangement itself or the circumstance that in these individuals could be enforced to discontinue RAASI medications with prognostic consequences at mid- to long-term. Purpose: Assess associations between management of RAASI and clinical outcomes among individuals with chronic cardiovascular conditions and hyperkalemia. Methods: Data from more than 375, 000 individuals 55 years of age or older were analyzed, in a population-based healthcare database of a public Institute of Health between 2015 and 2017. We conducted a longitudinal analysis, in which participants with at least one relevant condition were included: chronic heart failure, chronic kidney disease, diabetes mellitus, ischemic heart disease or hypertension. They had to be under RAASI treatment as of January 1st, 2016, and with evidence of at least one episode of hyperkalemia (serum potassium >5.0 mmol/L) during 2016. Then, were classified in one of the two following profiles: RAASI treatment discontinuation or down-titration versus RAASI treatment unchanged or up-titrated. Subsequently, all-cause death and hospitalization has been assessed in the follow-up period as clinical outcomes. For the statistical analysis, we calculated unadjusted incidence rate ratios and Cox Proportional Hazards Regression models to calculate the multivariable-adjusted risk ratios for the clinical endpoints comparing both groups. Results: There was found an association with mortality and hospitalization for the RAASI treatment interruption/down-titration group when compared unadjusted incidence rate ratios of each clinical endpoints to RAASI treatment unchanged patients (reference group). We presented these results in a Kaplan-Meier survivor curves for endpoint mortality (Figure 1). In the multivariable-adjusted model, the risk of mortality and hospitalization was associated mainly with older age, hypokalemia and down-titration of RAASI treatments, achieving statistical significance (Table 1). The risk ratio for mortality associated with down-titration and with hyperkalemia compared with the reference group was 1.676 (95% CI 1.54–1.82) and 1.161 (95% CI 1.07–1.26) respectively. Conclusion: These results suggest that the worse outcomes in hyperkalemia individuals could be influenced more for the discontinuation of RAASI prognostic drugs then for the hyperkalemia itself. It is necessary clinical randomized trials to confirm this observational hypothesis. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Josep Comin-Colet has received speaker fees from Vifor Pharma